EVALUASI PENERAPAN PAJAK PERTAMBAHAN NILAI ATAS JASA LOGISTIK ALAT BERAT PADA PT. VINTAMA PERKASA NUSANTARA - Maria Damayanti; Endang Mahpudin; Madjidainun Rahma (Journal of Economic, Bussines and Accounting (COSTING), 2026)
This study aims to evaluate, examine, and assess whether the Value Added Tax practices implemented by PT. Vintama Perkasa Nusantara as a heavy equipment logistics service provider have been implemented in accordance with applicable provisions and regulations. In this study, the researcher used a qualitative descriptive research type, using primary data sources and supporting data obtained through data collection methods through interviews and documentation activities. Based on the results of the research conducted, it was found that PT. Vintama Perkasa Nusantara can be said to have implemented Value Added Tax practices at a fairly good level, but there are several suggestions that can be considered for future implementation. Considering the importance of the contribution of Value Added Tax to state revenue, it is necessary to ensure that all companies that have been confirmed as Taxable Entrepreneurs have implemented Value Added Tax practices appropriately and appropriately. Through the evaluation process, it is hoped that companies can implement the suggestions given to implement corrective measures and increase company compliance with tax activities in Indonesia. Keywords : Heavy Equipment Logistics Industry, Tax, Value Added Tax